2021
DOI: 10.1038/s41467-021-24816-z
|View full text |Cite
|
Sign up to set email alerts
|

Insulin signaling regulates longevity through protein phosphorylation in Caenorhabditis elegans

Abstract: Insulin/IGF-1 Signaling (IIS) is known to constrain longevity by inhibiting the transcription factor FOXO. How phosphorylation mediated by IIS kinases regulates lifespan beyond FOXO remains unclear. Here, we profile IIS-dependent phosphorylation changes in a large-scale quantitative phosphoproteomic analysis of wild-type and three IIS mutant Caenorhabditis elegans strains. We quantify more than 15,000 phosphosites and find that 476 of these are differentially phosphorylated in the long-lived daf-2/insulin rece… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 82 publications
2
52
1
Order By: Relevance
“…Although inhibition of mTORC1 has received widespread enthusiasm as an anti-ageing strategy, mTORC1 maintains fundamental processes that include protein synthesis, mRNA splicing, and metabolic pathways 2,3,[48][49][50] , suggesting that not all effects of mTORC1 suppression are necessarily beneficial. Similarly, although conditions that suppress ISR signalling can promote longevity through effects on selective translation 15 , ISR signalling through eIF2 contributes to lifespan extension from reduced insulin/IGF-1 signalling 24 , and our results demonstrate that the downstream ISR effector ATF-4 is a potent pro-longevity factor. Furthermore, while pharmacological ISR inhibition preserves cognitive functions during ageing by maintaining protein synthesis 14,16 , our findings suggest that ISR suppression could reduce levels of H2S, which has been shown to prevent neurodegeneration 51,52 .…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Although inhibition of mTORC1 has received widespread enthusiasm as an anti-ageing strategy, mTORC1 maintains fundamental processes that include protein synthesis, mRNA splicing, and metabolic pathways 2,3,[48][49][50] , suggesting that not all effects of mTORC1 suppression are necessarily beneficial. Similarly, although conditions that suppress ISR signalling can promote longevity through effects on selective translation 15 , ISR signalling through eIF2 contributes to lifespan extension from reduced insulin/IGF-1 signalling 24 , and our results demonstrate that the downstream ISR effector ATF-4 is a potent pro-longevity factor. Furthermore, while pharmacological ISR inhibition preserves cognitive functions during ageing by maintaining protein synthesis 14,16 , our findings suggest that ISR suppression could reduce levels of H2S, which has been shown to prevent neurodegeneration 51,52 .…”
Section: Discussionsupporting
confidence: 61%
“…We next investigated whether translation inhibition might increase lifespan independently of this canonical ISR signalling, using a well-characterized eIF2 mutant (eif2(qd338)) in which the serine at which inhibitory phosphorylation occurs during the ISR (S49 in C. elegans; S51 in mammals) is mutated to phenylalanine, so that eIF2 phosphorylation and ISR induction are blocked 23 . A mutation that prevents phosphorylation of this serine partially suppresses lifespan extension from reduced insulin/IGF-1 signalling, suggesting that ISR signalling is important for longevity in this context 24 . Importantly, the eif2(qd338) mutation did not interfere with the atf-4dependent increase in lifespan that was seen with ifg-1 knockdown (Fig.…”
Section: Atf-4 Responds To Translation Suppression To Increase C Elegans Lifespanmentioning
confidence: 99%
“…IIS is a master regulator of glucose metabolism and lipid metabolism across the animal kingdom (Chatterjee and Perrimon, 2021;Zhang and Liu, 2014). In C. elegans, IIS also positively regulates protein synthesis (Li et al, 2021;Stout et al, 2013). The transcriptional changes shared by whole-body and intestinespecific DAF-2 degradation include up-regulation of peroxisome and fatty acid degradation, and down-regulation of RNA and protein metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, RNA-seq analysis underscored down-regulation of genes functioning in protein and RNA metabolism as common features shared by daf-2(e1370), whole-body, and intestinespecific DAF-2 AID (Figure 6A and 6B). Previous studies have shown that decreasing protein synthesis extends lifespan (Depuydt et al, 2013;Lan et al, 2019;Pan et al, 2007;Syntichaki et al, 2007;Tiku et al, 2017) and accounts for ~40% of the lifespan extension by daf-2(e1370) (Li et al, 2021). In comparison, little is known about how down-regulation of RNA metabolism contributes to daf-2 longevity.…”
Section: The Long-lived Animals Lacking the Insulin/igf-1 Receptor In The Intestine Redefine The Molecular Signature Of Longevitymentioning
confidence: 99%
See 1 more Smart Citation